Transcriptome Profiling of Leaf Elongation Zone under Drought in Contrasting Rice Cultivars - Cal, Andrew J. (Public Library of Science, 2013)
Inhibition of leaf elongation and expansion is one of the earliest responses of rice to water deficit. Despite this sensitivity, a great deal of genetic variation exists in the extant of leaf elongation rate (LER) reduction in response to declining soil moisture. We analyzed global gene expression in the leaf elongation zone under drought in two rice cultivars with disparate LER sensitivities to water stress. We found little overlap in gene regulation between the two varieties under moderate drought; however, the transcriptional response to severe drought was more conserved. In response to moderate drought, we found several genes related to secondary cell wall deposition that were down regulated in Moroberekan, an LER tolerant variety, but up-regulated in LER sensitive variety IR64.